Mast cell involvement in human cervical ripening. (July 2019) - Norström, Anders; Vukas Radulovic, Nina; Bullarbo, Maria; Ekerhovd, Erling
Abstract: Objective: Cervical ripening resembles an inflammatory process in many aspects, involving invasion of inflammatory cells, collagen breakdown and remodelling of the extracellular matrix. Mast cells produce a variety of inflammatory agents and are attributed a functional role in cervical ripening. The aim of this study was to examine if cervical mast cells are increased in number and stimulated during pregnancy. Study design: Cervical biopsies were obtained with a biopsy needle prior to surgical termination of pregnancy in the first trimester, surgery for first-trimester miscarriage, elective caesarean section, and benign gynaecological surgery in non-pregnant women. After fixation, semithin sections were prepared and stained with toluidine blue. The number of mast cells was counted under a light microscope and their secretory activity was scored (0.5–4) according to specified criteria and further visualised with electron microscopy. For pairwise comparison between groups Fisher's nonparametric permutation test was used. Results: The number of mast cells was increased from 3.4 ± 1.65 mast cells per 10 visual fields in non-pregnant women to 7.70 ± 0.35 per 10 visual fields in first trimester control women (p < 0.05). The highest number of mast cells was observed at term with 10.8 ± 2.1 per 10 visual fields, a number that was significantly higher than in first trimester control women (p < 0.05). At term mast cell activity scores were 3.39 ± 0.37 compared with 2.69 ± 0.27 in control first trimester women and 2.21 ± 0.86 in women with missed miscarriage (p < 0.05). The percentage of mast cells with activity score 4 was significantly higher at term compared with in the first trimester. Free mast cell granules were predominantly observed in areas with disorganized collagen fibres. Conclusion: The findings confirm that an increased influx of mast cells to the cervix occurs during pregnancy. The stimulated mast cell secretory activity in conditions associated with cervical tissue remodelling, such as term pregnancy and symptomatic miscarriage, provides further evidence that mast cells play a physiological role in cervical ripening.